Norway : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents key findings of Norway's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Banking Supervision, Insurance Regulation, and Payment Systems. Norway's financial system appears sound and well managed. Short-term vulnerabilities appear low overall, given improved macroeconomic conditions and historically low interest rates, coupled with generally prudent and transparent policies. Beyond the short term, however, rising household debt levels are the most important potential risk factor and will need to be watched closely.